The Second World War and its new world of wines, with comparative reference to South Africa and the USA c. 1939 - 1945 - Du Toit, Daniel S. R. (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2016.